(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The effect of the methanolic leaf extract of Hydrocotyle javanica (family Hydrocharitaceae) was investigated in mice to evaluate its antidiarrheal activity on magnesium sulfate (MgSO4) induced diarrhea and gastrointestinal motility. Hydrocotyle javanica, at doses of 50 mg/kg and 100 mg/kg, was tested for its effect on fecal output in magnesium sulfate induced diarrhea in albino mice and the results (percentage of animals showing diarrhea) were compared with those of diphenoxylate hydrochloride, a standard allopathic antidiarrheal drug. Hydrocotyle javanica ( at a dose of 100 mg/kg) inhibited the magnesium sulfate induced diarrhea and also reduced gastrointestinal motility in mice. The results indicate that the leaf extract significantly reduced diarrhea in mice with a reduction in weight of stools.